KONTEMPLASI PANCASILA DALAM TAUHID - roestamy, martin (Jurnal Sosial Humaniora, 2010)
Pancasila as a stateâs foundation of Indonesia has been evaluated, criticized, and reviewed intensively in the reformation era. Islam as a way of life of most Indonesian people also took a part in this very important step. By using contemplation method, wicth is based on philosophy or tafakkur. Pancasila has been found as parallel to Islam or tauhid point of view. The reason of this can be traced to the history where Islamic principle has been accommodated greatly in the process of Pancasila emergence. On the other hand, by contemplating Pancasila over aqidah, syariah, muamalah, and akhlaqul karimah that integrated in tauhid principle is a part to understand Indonesiaâs pluralist that parallel with achievement to kaffah as a muslim and the stronger Indonesia as well